Perfluorooctanoic Acid and Perfluorooctane Sulfonate Released from a Waste Water Treatment Plant in Bavaria, Germany - Becker, Anna; Suchan, Magdalena; Gerstmann, Silke; Frank, Hartmut (Environmental Science and Pollution Research, 2010)
Perfluorooctanoate (PFOA), perfluorooctane sulfonate (PFOS), and precursors and derivatives thereof have been employed as surfactants and anti-adhesives. PFOA and PFOS are environmentally persistent and the discharge of municipal waste waters is one of the principal routes of these compounds into the aquatic environment. In a previous study, the concentrations of PFOA and PFOS in grab samples collected from the waste water treatment plant (WWTP) of Bayreuth, a city of 72,000 inhabitants in Bavaria, Germany, during two periods showed considerable variability. For a better estimate of average mass flows, the surfactants were monitored (five samplings) from 16 March to 18 May 2007. In a second campaign, river water receiving the WWTP effluent was sampled twice a day for five consecutive day
Keywords: HPLC-ESI-MS/MS; Perfluorooctanoic acid; Perfluorooctane sulfonate; River water; Waste water; Perfluoroalkyl surfactants